CELEBRITY ENDORSEMENT AND EMOTIONAL APPEAL: A STUDY ON ADVERTISEMENTS BY POPULAR TAMIL CINEMA ACTORS - Dr. Rajesh R (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Advertising industries have executed various techniques in persuading customers to increase constructive responses about their products and services. Celebrity endorsement, one such popular advertising technique employed in influencing the customers. The construction of Brand or Product promotion that engages a popular personality using the reputation of the Brand, Product, or service is known as celebrity endorsement. That is, a celebrity endorsement is a promotional approach of a brand or product recommended by the famous person in the society to the customers or buyers. Here, the notable thing is that the celebrity endorses the brand or product powerfully evoking emotional feelings instead of usual appeal to the customers. In the fast movie world, the public likely to pay less attention to any advertisements in printed or visual form but optimistically get noticed when the advertisements are referred or recommended by their favorite celebrity. People in country like India, always grace about their stars from sports, politics, and particularly from the film industry. This article analyzes and evaluates various celebrity endorsements and emotional appeal, particularly the Tamil cinema actors